Seagrass (Enhalus acoroides) Restoration Performance with Two Different Methods (Anchor and Seed) in Panjang Island, Jepara, Indonesia - Jan Ericson Wismar; Ambariyanto; Widianingsih (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research Seeds can grow into seagrass seedlings for an optimal period of five weeks Seed sowing can be optimized by supplementing nutrients with fertilizers The seedling transplant method, which utilizes seed seedlings, is not significantly different in daily growth from the anchor transplant method, which utilizes donors/seeds transport The biomass content of seagrass leaves can be used to determine the growth rate of the leaves Abstract Globally, the area of seagrass beds important to the ecosystems in coastal environment is decreasing due to environmental pressures, both natural and artificial. Transplantation is one way to restore the condition of damaged seagrass beds, the anchor transplant method uses the transfer of donor seagrass to the transplant area, while the seed transplant method uses seed sowed from seagrass. This study aimed to investigate the survival and growth rates of seagrass transplants and the biomass and chlorophyll content of transplanted Enhalus acoroides in the waters of Panjang Island Jepara utilizing anchor and seedling methods. The research was conducted in the waters around Panjang Island, Jepara, between September and December 2021. The results indicated that transplantation of seagrass E. acoroides using the anchor method resulted in the highest average growth rate of 0.25 cm/day and a survival rate of 96.67%, while transplantation using the seedling method resulted in a growth rate of 0.18 cm/day and a survival rate of 83.33%. The results showed that the anchor method scored better than the seedling transplantation method in terms of growth rate and survival rate. However, seedling is a feasible method to meet the availability of seeds that will later be transplanted, considering that the anchor method still has shortcomings in terms of the availability of seeds and the use of pegs which are still not environmentally friendly. so that the seedling method can be recommended for the restoration process of seagrass ecosystems by taking into account the season, weather and other important indices.